2014
DOI: 10.1016/j.cub.2014.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Ancestry Patterns in Rapanui Suggest Pre-European Admixture with Native Americans

Abstract: These genetic results can be explained by one or more pre-European trans-Pacific contacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 42 publications
4
43
1
2
Order By: Relevance
“…Whether this reflects a post-settlement arrival of Amerindians to Easter Island and/or an eastern Polynesian return voyage to South America, remains unclear. Human ancient DNA studies have attested to the Rapanui people being of Polynesian descent (Hagelberg et al, 1994), yet recent research has identified Native American admixture-attributed to pre-European Native American contact (Moreno-Mayar et al, 2014;Thorsby, 2016). Technical and cultural concerns toward the sequencing, storage and interpretation of indigenous human DNA in the Pacific however, has limited access to human genetic material in this region, leaving such questions unresolved for the time being.…”
Section: Introductionmentioning
confidence: 99%
“…Whether this reflects a post-settlement arrival of Amerindians to Easter Island and/or an eastern Polynesian return voyage to South America, remains unclear. Human ancient DNA studies have attested to the Rapanui people being of Polynesian descent (Hagelberg et al, 1994), yet recent research has identified Native American admixture-attributed to pre-European Native American contact (Moreno-Mayar et al, 2014;Thorsby, 2016). Technical and cultural concerns toward the sequencing, storage and interpretation of indigenous human DNA in the Pacific however, has limited access to human genetic material in this region, leaving such questions unresolved for the time being.…”
Section: Introductionmentioning
confidence: 99%
“…These observations, together with the evident lack of strong geographic barriers in the country, make presentday Denmark an interesting setting for studying the genetic history of small populations with a glorious past. In recent years, there has been an explosion of human genetic studies that contributed substantially to the characterization of worldwide variation patterns (Lao et al 2008;Li et al 2008;Novembre et al 2008;Reich et al 2009;Busby et al 2015); the reconstruction of population history in regions with poor/nonexistent historical records (Moreno-Estrada et al 2014;Moreno-Mayar et al 2014); the study of local and global patterns of admixture in multiethnic societies (Bryc et al 2015); and the study of admixture with other hominin species as well as its use in elucidating human dispersals (Green et al 2010;Reich et al 2011). The increased power of high-throughput genotype data and computational methods has also boosted the emergence of many single-country genomic projects in Europe (Jakkula et al 2008;Price et al 2009; Genome of the Netherlands Consortium 2014; Karakachoff et al 2015;Leslie et al 2015) and the release of useful data to the public (Welter et al 2014).…”
mentioning
confidence: 99%
“…This study focused on genetic data derived from 27 modern Rapa Nui. By assaying for genetic variability across the nuclear genome Moreno-Mayar et al [104] were able to disentangle portions of the genomes showing shared sequences with Polynesia, as expected, as well as the Americas and Europe. Further, by modeling demographic scenarios, the authors were able to estimate that the likely timing of the admixture between Rapa Nui and Native Americans pre-dated Europeans.…”
Section: Modern Dnamentioning
confidence: 86%
“…Here, we focus on three high-profile cases of new claims that support Jones and Klar's model of Polynesian-American contact: (1) direct evidence for transfer of the domesticated chicken (Gallus gallus) from Polynesia to South America [96][97][98][99][100][101][102]; and, (2) skulls of two Polynesians within collections of human remains attributed to a Native American group in Central-Eastern Brazil (Botocudo) [103]; and, (3) full genomic study of modern Rapa Nui indicating pre-European contact admixture with Native Americans [104].…”
Section: Long-distance Contacts Between Polynesians and Native Americasmentioning
confidence: 91%